Revision Ulnar Collateral Ligament Reconstruction in Professional Baseball: Current Trends, Surgical Techniques, and Outcomes. Issue 8 (12th August 2019) - Camp, Christopher L.; Desai, Vishal; Conte, Stan; Ahmad, Christopher S.; Ciccotti, Michael; Dines, Joshua S.; Altchek, David W.; D'Angelo, John; Griffith, Timothy B.
Background: Ulnar collateral ligament (UCL) reconstruction of the elbow is commonly performed on professional baseball pitchers. Recent reports have suggested that revision rates are on the rise and may be higher than previously thought. Purpose: To provide a comprehensive report on current trends, surgical techniques, and outcomes of revision UCL reconstructions performed on professional baseball pitchers between 2010 and 2016. Study Design: Case series; Level of evidence, 4. Methods: The Major League Baseball Health and Injury Tracking System (HITS) was used to compile records of all revision UCL reconstructions performed on professional baseball pitchers between 2010 and 2016. Player data and outcomes were obtained from HITS, and surgical details were obtained from operative reports. Descriptive statistical analysis was performed on epidemiologic data. Outcomes (return to play [RTP] rates, RTP times, subsequent injuries, and subsequent surgeries) were compared across the most common surgical techniques (docking vs modified Jobe) and graft sources (palmaris longus autograft vs hamstring autograft). Results: A total of 69 professional baseball pitchers underwent revision UCL reconstruction from 2010 to 2016 at an average of 1424 days (47 months) after their primary surgery. A trend was seen toward increasing numbers of revision surgeries over time ( R 2 = 0.441; P = .104). The most commonly used tunnel configuration was the modified Jobe technique (n = 41; 59.4%), and the most commonly used graft was hamstring autograft (n = 34; 49.3%). A majority (76.6%) of pitchers achieved RTP, and 55.3% were able to return to the same level of play. Mean time to RTP was 436 days (14.5 months) for players with a palmaris longus autograft versus 540 days (18 months) for those with a hamstring autograft ( P = .108). Further, the mean time to RTP was 423 days (14 months) for the docking technique versus 519 days (17 months) for the modified Jobe technique ( P = .296). Similar rates of subsequent injuries and surgeries were noted between the 2 revision techniques and 2 most commonly used graft constructs. Conclusion: Revision UCL reconstruction showed relatively high RTP rates (77%), but only 55% of players returned to their same level of play. Mean time to RTP was shorter than that found in other, smaller investigations. Although general trends were seen toward decreased time to RTP for the docking technique and palmaris longus autograft, these differences did not reach statistical significance.